Ureteral stent biomaterial encrustation after endoscopic lithotripsy: a randomized, single-blind study - Shuzo Hamamoto; Ryosuke Chaya; Kazumi Taguchi; Takaaki Inoue; Shinsuke Okada; Chatporn Boonyapalanant; Masahiko Isogai; Kengo Kawase; Koei Torii; Rei Unno; Atsushi Okada; Takahiro Yasui (Scientific Reports)
Abstract This study evaluated the adherence of bacteria, calcium, and magnesium to three different ureteral stents after endoscopic surgery for urinary calculi. We randomly assigned 61 patients requiring the insertion of ureteral stents after urinary calculi treatment into three groups: Percuflex with a coating composition of Hydroplus (n = 21); Tria with a coating composition of Percushied (n = 22); and InLay Optima, which had a proprietary pHreeCoat coating (n = 18). All stents were removed and evaluated 1 month after treatment. The primary outcome was biomineral attachment to the ureteral stent. Calcium and magnesium contents were measured using atomic absorption spectrometry after the stent had been vortexed in a solution of saline and hydrochloric acid at pH 2. Bacteria were measured through flow cytometry of the washing solution collected by decantation after stent fragments had been immersed and vortexed in a saline solution. Median amounts of calcium and magnesium adhered to Percuflex were significantly higher than those adhered to Tria and InLay Optima. The median number of bacteria adhered was also highest in Percuflex compared to that in the other two groups, although without a statistically significant difference. These findings suggest that selecting stents with superior coating materials enhances patient outcomes and reduces stent-related complications.